Pemanfaatan Instagram Solo Safari sebagai Promosi untuk Meningkatkan Minat Kunjungan - Saputra, Ryan Denata; Peranginangin, Jasanta; Suharto, Suharto (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
In today's digital age, social media has become the primary means of promoting tourism. Instagram, as a visual platform, allows information to be conveyed to locations through aesthetic, interactive, and easily accessible content. The Solo Safari educational and conservation tourist destination in Surakarta City uses its official Instagram account, @solosafari.id, to build its image, reach a wide audience, and increase tourist interest. The purpose of this study is to examine the use of Solo Safari's Instagram as a promotional medium, identify useful content indicators, and discover problems and opportunities in its management. Descriptive qualitative research was used, with data collection through observation, interviews, and documentation. Data analysis used the Miles & Huberman model, which includes presentation, verification, and reduction. The results of the study indicate that Solo Safari's Instagram content, which emphasizes visual aesthetics, storytelling, information relevance, consistency of posts, and interactivity, plays a significant role in increasing the number of visits received. However, changes in Instagram's algorithm, rapid changes in digital trends, and limited human resources for content management are new problems. This study found that Instagram is an effective tool for promoting educational tourist destinations. Destination managers can use it to gain new ideas.